Unraveling Host-Gut Microbiota Dialogue and Its Impact on Cholesterol Levels - Villette, Remy; KC, Pukar; Beliard, Sophie; Salas Tapia, Maria Fernanda; Rainteau, Dominique; Guerin, Maryse; Lesnik, Philippe (Frontiers in Pharmacology, 2020)
Disruption in cholesterol metabolism, particularly hypercholesterolemia, is a significant cause of atherosclerosis cardiovascular disease. Large interindividual variations in plasma cholesterol levels are traditionally related to genetic factors, and the remaining portion of their variance is accredited to environmental factors. In recent years, the essential role played by intestinal microbiota in human health and diseases has emerged. Gut microbiota is currently viewed as a fundamental regulator of host metabolism and of innate and adaptive immunity. Its composition in bacteria but also the synthesis of multiple molecules resulting from bacterial metabolism vary according to diet, antibiotics, drug used and the exposure to pollutants as well as infectious agents. Microbiota modifications induced by recent changes in the human environment thus seem to be a major factor in the current epidemic of metabolic/inflammatory diseases (diabetes mellitus, liver diseases, inflammatory bowel disease, obesity, and dyslipidemia). Epidemiological and preclinical studies report associations between bacterial communities and cholesterolemia. However, such an association remains poorly investigated and characterized. The objectives of this review are to present the current knowledge and potential mechanisms underlying the host-microbiota dialogue for a better understanding of the contribution of microbial communities to the regulation of cholesterol homeostasis.